A proposed protocol for GMP-BoK gap analysis: case study at AASTMT - Gamal Ahmed Mohamed Ghalwash; Mahmoud S. El-Bawab; Ahmed A. Swidan; Mohamed S. Rowihil; Amr M. Ibrahim; Yasser B. A. Farag (Maritime Research and Technology)
The International Association of Maritime Universities (IAMU) developed the Global Maritime Professional Body of Knowledge (GMP-BoK) to address the current gap between the maritime industry expectations and the delivered maritime education and training (MET) programs. This paper briefly introduces the GMP-BoK and investigates the effectiveness of a new analogous instrument to efficiently implement the GMP-BoK via a user-friendly method developed at the Arab Academy for Science, Technology and Maritime Transport (AASTMT). The analogous instrument helps maritime universities and institutes to digitalize and develop an integrated curriculum framework based on robust evaluation and data analysis to develop strategic plans to improve seafarer capabilities. The paper suggests a protocol for mapping and analyzing maritime programs and courses, enabling educators to reliably perform gap analysis and identify repetitions within delivered courses and programs based on the GMP-BoK recommended practices. As a case study, the proposed protocol was validated utilizing the Maritime Engineering Technology Program (METP). The findings of this study showed that the examined METP includes 30% repetition and focuses on the cognitive and psychomotor methods of education, with little focus on the affective technique. The presented simple protocol can be applied by maritime universities and institutes seeking to evaluate their programs with regard to the GMP-BoK recommendations.